Anti-inflammatory cytokines in asthma and allergy: interleukin-10, interleukin-12, interferon-gamma. - Chung, F (2001)
Interleukin-10 (IL-10) is a cytokine derived from CD4+ T-helper type 2 (T(H2)) cells identified as a suppressor of cytokines from T-helper type 1(T(H1)) cells. Interleukin-12 (IL-12) is produced by B cells, macrophages and dendritic cells, and primarily regulates T(H1) cell differentiation, while suppressing the expansion of T(H2) cell clones. Interferon-gamma (IFN-gamma) is a product of T(H1) cells and exerts inhibitory effects on T(H2) cell differentiation. These cytokines have been implicated in the pathogenesis of asthma and allergies. In this context, IL-12 and IFN-gamma production in asthma have been found to be decreased, and this may reduce their capacity to inhibit IgE synthesis and allergic inflammation. IL-10 is a potent inhibitor of monocyte/macrophage function, suppressing the production of many pro-inflammatory cytokines. A relative underproduction of IL-10 from alveolar macrophages of atopic asthmatics has been reported. Therapeutic modulation of T(H1)/T(H2) imbalance in asthma and allergy by mycobacterial vaccine, specific immunotherapy and cytoline-guanosine dinucleotide motif may lead to increases in IL-12 and IFN-gamma production. Stimulation of IL-10 production by antigen-specific T-cells during immunotherapy may lead to anergy through inhibition of CD28-costimulatory molecule signalling by IL-10s anti-inflammatory effect on basophils, mast cells and eosinophils.